2018
DOI: 10.18535/ijsrm/v6i6.ah02
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Household Food Insecurity: The Case of West Belesa, North Gondar, Amhara Region, Ethiopia

Abstract: The vast majority of extraordinarily poor households live in rural areas that are heavily reliant on rain fed agriculture. In Ethiopia, the Amhara region in particular, has been prone to much suffering in the past, and was one of the hardest hit areas. Different projects and programs were designed and implemented to reduce household food insecurity. However, the effect of the program whether household food insecurity is reduced or not was not yet assessed in these areas. This is therefore, to investigate the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…The chi-square test revealed that there was an association between food security status and sex of household and was statistically significant at p ≤ 0.01. The finding was consistent with the empirical findings of Yehuala et al (2018). According to a study conducted in South Africa by Sekhampu (2013), the female-headed households had better food security than the male-headed households due to the small size of family members that existed in a femaleheaded household.…”
Section: Nexus Between Food Security Status and Household Socio-econo...supporting
confidence: 88%
See 1 more Smart Citation
“…The chi-square test revealed that there was an association between food security status and sex of household and was statistically significant at p ≤ 0.01. The finding was consistent with the empirical findings of Yehuala et al (2018). According to a study conducted in South Africa by Sekhampu (2013), the female-headed households had better food security than the male-headed households due to the small size of family members that existed in a femaleheaded household.…”
Section: Nexus Between Food Security Status and Household Socio-econo...supporting
confidence: 88%
“…The finding was coherent with the research finding of WFP ( 2019), and Abafita and Kim (2014) stated that literate households were better off, in terms of food security, as compared to households that were illiterate. However, it was not consistent with the findings of Yehuala et al (2018).…”
Section: Education Statuscontrasting
confidence: 84%
“…In an attempt to investigate the triggers of food insecurity, different methods have been employed (Crush et al, 2012; Frongillo et al, 2019; Fyles & Madramootoo, 2015). Some studies have employed a single equation model (Denny et al, 2018; Hadley et al, 2019; Magaña‐Lemus et al, 2016) whiles others have used other econometric techniques to justify this relationship (Burkhardt et al, 2012; Kebede et al, 2016; Yehuala et al, 2018). Our method sought to develop and utilize a high degree of accuracy modeling and food insecurity forecasting approach not based on assumptions and scenarios that can predict food insecurity for the long‐term.…”
Section: Methodsmentioning
confidence: 99%
“…According to Niankara (2023), the more the number of family members, the greater the need for food and the lower the level of food security. Several studies have shown that households with fewer members had better food security than households with a greater family members (Endale et al, 2014;Welderufael & Welderufael, 2014;Yehuala et al, 2018;Sani & Kemaw, 2019;Mabuza & Mamba, 2022). .…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%